Effects of tea residues-fermented feed on production performance, egg quality, antioxidant capacity, caecal microbiota, and ammonia emissions of laying hens - Chen, Xianxin; Zhou, Xinhong; Li, Shiyi; Zhang, Huaidan; Liu, Zhenkun (Frontiers in Veterinary Science, 2023)
This study was to assess the effects of tea residues-fermented feed (TR-fermented feed) on production performance, egg quality, serum antioxidant capacity, caecal microbiota, and ammonia emissions of laying hens. A total of 1,296 Lohmann laying hens have randomly distributed four groups with six parallels and fed with diets TR-fermented feed at the rates of 0 (control), 1, 3, and 5%. The inclusion of 1% (TR)-fermented feed resulted in a significant increase in egg-laying rate and average egg weight of birds, and a reduction in the feed-to-egg ratio when compared to the control group (p < 0.05). The addition of 1 and 3% of (TR)-fermented feed significantly improved the Haugh unit of eggs (p < 0.05). The eggshell thickness was observed to increase by almost one-fold upon the inclusion of 3 and 5% (TR)-fermented feed in the basal diet (p < 0.05). The supplementation of 3% (TR)-fermented feed significantly increased the content of methionine, tyrosine, proline, essential amino acids (EAA), alpha linoleic acid (C18:3n6), docosanoic acid (C22:0), docosahexaenoic acid (C22:6n3), twenty-three carbonic acids (C23:0), ditetradecenoic acid (C24:1) and total omega-3 polyunsaturated fatty acids (∑ω-3 PUFA) in the eggs (p < 0.05). The addition of a certain amount of (TR)-fermented feed can enhance the activity of glutathione peroxidase (GSH-PX) and superoxide dismutase (SOD) in chicken serum, and reduce the level of malondialdehyde (MDA) (p < 0.05). The ammonia concentration in the hen house of laying hens in the treatment groups decreased significantly (p < 0.05). Bacteroidetes and Firmicutes, the main phyla in the cecal bacterial community, were differentially abundant in each group, comprising greater than 55 and 33%, respectively. Collectively, this research indicates that (TR)-fermented feed supplementation improves the performance of laying hens and reduces ammonia emissions and can be used in industry-scale layer production.